Modeling Simulation of Tidal Flows in Jakarta Bay Waters - Awaluddin, Awaluddin; Santosa, Yoyok Nurkaya; Bakri, Muhammad; Hawati, Hawati; Malik, Kurnia; Pranowo, Widodo Setiyo (PONGGAWA : Journal of Fisheries Socio-Economic, 2024)
Jakarta Bay is one of the important waters in Indonesia that plays a major role in economic activities, shipping, defense, and coastal tourism. Therefore, field observations and numerical modeling with Mike 21 are needed to determine the pattern of tidal current movement. Field observations of currents and tides were carried out for 15 days at the marina beach where the observation data will later be processed using the admiralty method to determine the harmonic component and tidal type and the observation data is used to validate the data from the MIKE 21 modeling simulation. The tidal validation results got an RMSE value of 0.13 with a correlation of 0.95 and the current validation results got an RMSE value of 0.05 with a correlation of 0.14.